ANALYSIS OF TESTING APPLICATIONS FOR LEARNING POLITENESS IN LANGUAGE FOR DIGITAL LEARNING THERAPY ON STUDENTS OF SMK N 7 MEDAN - Yunus, Rusyda Nazhirah; Putri, Ranti Eka (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Generation Z children who are familiar with the convenience of technology but tend to be individualistic individuals require a balance between knowledge and skills as the basis of quality human resources in the times. Honing language politeness skills through self-habituation based on knowledge is a must. Language politeness among generation Z students tends to decrease in politeness compared to ancient times. This can be seen in the expressions or writings in voicing their opinions and feelings through social media. We often hear, read, and witness the habits of today's students who lightly utter harsh words, hate speech and sometimes also accompanied by a condiment between friends which is sad to hear. This phenomenon shows a decrease in language politeness which is not only related to the choice of words or sentences but also related to global social customs and information that has an influence on culture, especially with regard to politeness values. In the end, they have linguistic rules that are considered prestigious, regardless of the actual language rules. The object of this research is the students of SMKN 7 Medan. The data collection method in this research is the interview and documentation method. The results of this study are the formation of multimedia-based learning containing language politeness learning content about how to respect and appreciate, tell the truth, give praise, give greetings and greetings, make comments, give sympathy, apologize, use non-verbal language, all of this is presented. in the form of animation so that SMKN 7 students will be more interested in the process of learning language politeness.